Psychological distress and coping responses among occupational safety and health competent post-COVID-19 era in Malaysia - Mohd Ali, Fauzah Rahimah; Pasi, Hafizah; Ibrahim, Muhamad Arif; Zein, Raemy Mad; Yee, Joy Khong Chooi; Shariff, Ruzita Mohd; Salihen, Nur Alyani Fahmi (Intelektual Pustaka Media Utama, 2025)
Amidst the COVID-19 pandemic, mental health challenges have emerged, highlighting the need to identify psychological distress and coping strategies, particularly among occupational safety and health (OSH) competent persons. This is a cross-sectional study measuring stress, anxiety, and depression levels while exploring coping mechanisms among OSH professionals in Malaysia during the COVID-19 recovery phase, using DASS-21 and Brief-COPE questionnaires. The findings indicate that chronic illness increases the risk of depression (p=0.005) and stress (p=0.047). Higher income is associated with greater risks of depression (p<0.001) and stress (p<0.001). Monthly expenses exceeding budget limits heighten the risk of depression (p<0.001) and anxiety (p=0.024). Conversely, older age decreases the risk of both depression (p<0.001) and stress (p=0.001). Caring for family members affected by COVID-19 reduces depression (p<0.001) and stress (p<0.001). Having more monthly savings decreases the risk of depression (p<0.001) and anxiety (p=0.017). The study reveals that stress individuals prefer emotional focus coping (p=0.006). Addressing these factors is crucial for mitigating psychological distress among OSH professionals.